Sacred Calendar and Expression of Religion in Indonesia - Rosyad, Rifki; Wahyudin, Dede; Hamim, Mohamad; Sonjaya, Adang; Alam, Aam Saepul; Alam, Aam Saepul (International Journal of Psychosocial Rehabilitation, 2020)
This study elaborates the sacredness dimension and religious expression of Muslims in Indonesia in establishing sacred days. The objective of this paper is finding the ultimate values in the sacred day calendar application in Indonesia. This study applied library research approach which primarily refers to books, journals and proceedings as data resources. The research findings state some ultimate values in determining the sacred days in Indonesia: (1) religious doctrine can shape one’s total belief in certain objects, (2) religious rituals can build the solidarity of religious adherents, (3) religious institution is the representation of values that binds its adherents, (4) state authority is the determinant variable for religious groups existence, (5) Need and Achievement /NaCH. The need for ritual element will always exist in both primitive and modern societies. In order to create conducive atmosphere of religious pluralism, it is imperative for the state not to prohibit religious expression from any community because it is different from social action.